2021
DOI: 10.3390/ijms22020791
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Ubiquitin Signaling Cascade in Tumor Microenvironment for Cancer Therapy

Abstract: Tumor microenvironments are composed of a myriad of elements, both cellular (immune cells, cancer-associated fibroblasts, mesenchymal stem cells, etc.) and non-cellular (extracellular matrix, cytokines, growth factors, etc.), which collectively provide a permissive environment enabling tumor progression. In this review, we focused on the regulation of tumor microenvironment through ubiquitination. Ubiquitination is a reversible protein post-translational modification that regulates various key biological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 131 publications
(245 reference statements)
0
20
0
1
Order By: Relevance
“…MDM2 inhibitors work by inhibiting the E3 ligase activity of MDM2 and interfering with the MDM2-p53 interaction [ 162 , 211 ]. Many MDM2 inhibitors, with unique structure, high efficiency, and no peptides, have been successfully designed and developed [ 162 ], including Nutlin-3a [ 170 ], HLI98 [ 171 ], MEL23, and MEL24 [ 172 ].…”
Section: Therapeutic Targeting Of E3 Ligases In Cancer Immunotherapymentioning
confidence: 99%
“…MDM2 inhibitors work by inhibiting the E3 ligase activity of MDM2 and interfering with the MDM2-p53 interaction [ 162 , 211 ]. Many MDM2 inhibitors, with unique structure, high efficiency, and no peptides, have been successfully designed and developed [ 162 ], including Nutlin-3a [ 170 ], HLI98 [ 171 ], MEL23, and MEL24 [ 172 ].…”
Section: Therapeutic Targeting Of E3 Ligases In Cancer Immunotherapymentioning
confidence: 99%
“…These UbVs can inhibit HECT, monomeric RING/Ubox, or multi-subunit SCF RING E3 ligases or deubiquitinases. Alternatively, they can activate HECT or homodimeric RING E3 ligases (Ernst et al, 2013;Liu et al, 2021). In the case of RING/Ubox E3 ligases, inhibition occurs via blocking the E3ubiquitin binding surface and activation occurs via stabilization of the E2-ubiquitin interaction (Gabrielsen et al, 2017 demonstrated that with HECT E3 ligases, the UbV-based inhibition is due to blocking the E2 binding site, whereas activation is observed in response to UbV binding to the N-lobe exosite.…”
Section: Phage Display Assays To Identify Novel E3 Ligase Ligands or Substratesmentioning
confidence: 99%
“…Ubiquitination is a post-translational medication pathway involved in wide range of cellular functions, including autophagy, immune response, and DNA damage response ( Shaid et al, 2013 ). During ubiquitination, ubiquitin protein is attached to target proteins through catalysis pathway mediated by E1 ubiquitin-activating enzymes, E2 ubiquitin-conjugating enzymes and E3 ubiquitin ligases ( Liu et al, 2021 ). UAE and UBA6, both referred as E1 enzymes, are known to initiate ubiquitin conjugation by regulating cellular ubiquitin-charging ( Jin et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%